Virtual power plant/s (VPP) to facilitate frequency control regulation in Singapore’s power system - Lin, Tong Shen (Nanyang Technological University, 2020)
Solar energy has been viewed as the most feasible renewable energy option for Singapore to produce electricity due to its abundance of solar energy. However, the major drawback of using solar energy is the effects of intermittency where the supply of electricity generated by the Photovoltaic (PV) systems is dependent on the number of sun hours throughout the day. As such, PV systems are classified as Intermittent Distributed Generators (IDG). With the increased number of IDGs connected to the grid, the effects of intermittency are magnified which results in the disturbance to the electricity grid in achieving a balance of supply and demand.